The determinants of training effectiveness in Malaysian organizations - Mat Rashid, Kartini; Jusoff, Kamaruzaman (Institute of Interdisciplinary Business Research, 2010)
Training is one of the most pervasive methods for enhancing the productivity of individuals and communicating organizational goals to new personnel. It is a learning process that involves the acquisition of knowledge, sharpening of skills, concepts, rules, or changing of attitudes and behaviors to enhance the performance of employees. This paper examines the importance, relevance, and implications of training in organizations today, and attempts to identify the significant determinants of training effectiveness. By constructing a hypothetical research model to investigate the effect of four moderating variables on the training participants (independent variable) towards training effectiveness (dependent variable), a survey questionnaire was distributed to employees in various organizations who have attended training programs. Data from a sample size of 200 was obtained and subjected to reliability tests using Cronbach's Alpha, and the eight hypotheses drawn up from the research model were subjected to Two-way ANOVA tests of significance. Instructor competence and training type (in-house vs. external consultant) were found to be significant factors contributing to training effectiveness. Though not an exhaustive conclusion, this finding holds extensive implications for training in organizations and would pave the way for further research.